Ritual and narrative: theoretical explorations and historical case studies - Nünning, Vera; Rupp, Jan; Ahn, Gregor (transcript, 2013)
Ritual and narrative are pivotal means of human meaning-making and of ordering experience, but the close interrelationship between them has not as yet been given the attention it deserves. How can models and categories from narrative theory benefit the study of ritual, and what can we gain from concepts of ritual studies in analysing narrative? This book brings together a wide range of disciplinary perspectives including literary studies, archaeology, biblical and religious studies, and political science. It presents theoretical explorations as well as in-depth case studies of ritual and narrative in different media and historical contexts.
Keywords: Konferenzschrift -- 2011 -- Heidelberg; Soziale Funktion; Erzähltechnik; Ritual